Care for people with a problem related to alcohol abuse: an integrative literature review study (Research, Society and Development, 2020)
The use of psychoactive substances, mainly alcohol, has been a constant in human life. Objective: In this article, the objective was to understand the scientific production of Brazilian nursing on care for people with problems related to alcohol abuse. Method: The integrative literature review method was used, considering its six stages. Result: Accessing the databases Latin American and Caribbean Literature in Health Sciences (LILACS), Nursing Database (BDENF) and Scientific Electronic Library Online (SciELO), period between March and August 2019, 12 were selected articles. Conclusion: The use of alcohol marks the relationship between human beings, being present in different contexts, with objectives and motivations in different ways.